Semiotic Representations in School Algebra: A Systematic Review - Vásquez-Alvial, Isabella (2024)
The objective of this study was to assess the current state of research on the use of various semiotic representations in the teaching and learning of school algebra from 2013 to 2022. Given their nature, students can access mathematical objects only through representations that involve signs and symbols. The predominantly symbolic nature of modern mathematics raises important questions about how students acquire and internalize mathematical knowledge. To evaluate the use of semiotic representations in school algebra among secondary education students, a systematic review was conducted following the PRISMA guidelines. This review involved analyzing the themes and theoretical frameworks presented in the selected studies. The findings highlighted a diversity of representations and theoretical principles, yet also revealed a scarcity of research during the 2013-2022 period, a limited number of studies from Latin America, notable variety in the semiotic registers used in study designs, and a strong preference for sociocultural theories.